2010
DOI: 10.1038/onc.2010.273
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in mutant FLT3-positive AML

Abstract: Mutant Fms-Like Tyrosine kinase-3 (FLT3), which is expressed in the leukemic cells of a subpopulation of acute myeloid leukemia (AML) patients, represents an attractive target for the therapy of AML. There are several FLT3 inhibitors presently in clinical trials with sufficient efficacy and toxicity features to warrant further testing in combination with standard therapies. However, the transient and partial responses observed in AML patients treated with FLT3 inhibitors, coupled with the discovery of drug-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 160 publications
(158 reference statements)
0
74
0
Order By: Relevance
“…29,64 Mutant receptors such as Fms-like tyrosine kinase may induce Foxo-3a inactivation, which can lead to resistance to Fms-like tyrosine kinase inhibitors and result in a poor prognosis. 128,129 A diagram illustrating some of the effects of the PI3K/PTEN/Akt/mTOR pathway on apoptosis and drug resistance is presented in Figure 4.…”
Section: Pi3k/pten/akt/mtor Drug Resistance and Leukemia Therapymentioning
confidence: 99%
“…29,64 Mutant receptors such as Fms-like tyrosine kinase may induce Foxo-3a inactivation, which can lead to resistance to Fms-like tyrosine kinase inhibitors and result in a poor prognosis. 128,129 A diagram illustrating some of the effects of the PI3K/PTEN/Akt/mTOR pathway on apoptosis and drug resistance is presented in Figure 4.…”
Section: Pi3k/pten/akt/mtor Drug Resistance and Leukemia Therapymentioning
confidence: 99%
“…FLT3 is a class III receptor tyrosine kinase, which frequently carries mutations in patients with acute myeloid leukemia (AML) resulting in constitutive activation. 17 It has an important role in the homeostasis of DCs, and its ligand, FLT3L, has been used in several studies to activate these cells in vitro and in vivo. 18 --22 Thus, during characterization of SDIEMmodified FLT3 antibodies we put particular emphasis on the evaluation of antibody specificity and toxicity towards DCs and hematopoietic stem cells in addition to the exploration of ADCC activity.…”
Section: Introductionmentioning
confidence: 99%
“…115 Mutant receptors such as Flt-3 may induce Foxo-3a inactivation, which can lead to resistance to Flt-3 inhibitors and result in a poor prognosis. 51,117,118 Recently, it was demonstrated that Foxo-3a is inactive in AML cells and is localized in the cytoplasm. 119 Treatment of AMLs with MEK and PI3K/Akt inhibitors did not result in the nuclear translocation of Foxo-3a where it could potentially induce cell cycle inhibitory and apoptotic genes.…”
Section: -112mentioning
confidence: 99%